Conceptualising boys’ behaviour difficulties in terms of anxiety: A case study. - Redmond, Orla (2017)
Many pupils are marginalised within the education system, with long-term consequences in terms of poorer mental health and wellbeing, affecting life outcomes. Risk factors and indicators for anxiety suggest it may lie at the heart of increasing behavioural difficulties for boys, particularly given its link to anger, but this is little-recognised. This paper examines the implications of anxiety and considers the role teachers and school systems may play in exacerbating the problem. In an illustrative case study, managing anxiety (and the resultant behavioural ramifications) through an interpersonal and thinking skills programme is considered. A fourth dimension to the flight/fight/freeze response is proposed and guidelines for classroom practice suggested.